Numerical study of the air gap between fire-protective clothing and the skin. (September 2014) - Ghazy, Ahmed
The analysis of the air gap between fire-protective clothing and the skin plays a crucial role in evaluating the protective performance of the clothing. However, the more accurate the analysis of the air gap, the more complex the air-gap model. This article introduces a novel air-gap model that stands halfway in terms of accuracy and complexity between other two models that already exist in the literature. A comparison between the performances of fire-protective clothing predicted by using the three air-gap models is discussed in this article. Different parameters that affect heat transfer within the air gap and hence the protective performance of the clothing were studied to assess the novel air-gap model compared with the other two models. Despite its simplicity, the novel air-gap model predicted the performance of fire-protective clothing as accurately as the most realistic model.